Electromagnetic ice absorption rate at Dome C, Antarctica - Achille Zirizzotti; James A. Baskaradas; Stefano Urbini; Lili Cafarella (Journal of Glaciology, 2014)
AbstractRadio-echo sounding (RES) is a radar technique widely employed in Antarctica and Greenland to define bedrock topography but, over the last decade, it has also played an important role in subglacial lake exploration and hydrogeological studies at the bedrock/ice interface. In recent studies, bedrock characterization has been improved through analysis of radar power echoes to evaluate the electromagnetic (EM) properties of the interface and allow the distinction between wet and dry interfaces. The RES received signal power depends on ice absorption and bedrock reflectivity, which is closely linked to the specific physical condition of the bedrock. In this paper, an evaluation of EM ice absorption was conducted starting from RES measurements collected over subglacial lakes in Antarctica. The idea was to calculate ice absorption starting from the radar equation in the case of subglacial lakes, where the EM reflectivity value is considered a known constant. These values were compared with those obtained from analysis of ice-core dielectric profiles from EPICA ice-core drilling data. Our analysis reveals that the ice absorption rate calculated from RES measurements has an average value of 7.2 dB km−1, and it appears constant, independent of the subglacial lake depth in different zones of the Dome C area.